Leadership Skills for School Principals to Improve the Quality of School Management Through Training Management - Qarasyi, Achmad Qhuzairy; Yanto, Heri; Raharjo, Tri Joko; Yulianto, Arief (Proceedings of International Conference on Science, Education, and Technology, 2025)
Education and training management (diklat) is a key element in the development of competent and professional human resources. This research discusses effective strategies in training management, including planning, implementation, evaluation, and challenges faced in the implementation of training programs. With a qualitative descriptive approach, this study examines various methods to increase the effectiveness of training, including the use of digital technology, competency-based approaches, and the importance of continuous evaluation. The results of the study show that the effectiveness of training is greatly influenced by the readiness of the institution, systematic planning, and the involvement of participants in the learning process. This study contributes to providing insights for educational institutions and organizations in managing training more optimally to improve the quality of human resources in various sectors. Effective training management requires a combination of a well-thought-out planning strategy, organized implementation, and continuous evaluation. The application of digital technology and competency-based approaches has been proven to be able to increase the effectiveness of training programs. In addition, the success of the training is also greatly influenced by the commitment of the organization, the readiness of the trainers, and the active involvement of the participants. By applying the principles of training management optimally, educational institutions and organizations can improve the quality and competitiveness of human resources.